Sustaining Nurse‐Rapid HIV Testing in the U.S. Department of Veterans Affairs: Lessons Learned from a Comparative Evaluation. Issue 5 (3rd June 2013) - Solomon, Jeffrey L.; Bokhour, Barbara G.; Butler, Jaimi; Golden, Joya F.; Hare, Katherine; Kertz, Barbara; Kan, Virginia; Rodriguez‐Barradas, Maria; Knapp, Herschel; Anaya, Henry D.
Abstract Routine HIV testing in primary care is now recommended in the United States. The U.S. Department of Veterans Affairs (VA) has increased the number of patients tested for HIV, but overall HIV testing rates remain low. A promising intervention for increasing HIV testing is nurse‐initiated rapid testing (NRT). The purpose of this study was to build upon our previous research by implementing NRT in primary care clinics at two geographically distinct VA medical centers, and then conduct an evaluation to identify the barriers and facilitators to implementing and sustaining it. Semistructured telephone interviews were conducted with providers and stakeholders at two VA medical centers, one each on the East Coast and in the Southwest. Fieldnotes were developed following each interview and qualitatively coded for emerging themes. Findings indicate NRT was well integrated in both settings. NRT took little time to conduct, was well received by patients, and did not disrupt clinical scheduling. However, there were some sustainability challenges, including difficulties using the electronic medical record, and the challenges of new care practice structures. Implementing NRT is feasible in VA primary care settings. However, organizational challenges should be taken into account for subsequent efforts to implement NRT in VA primary care settings.